The Domestication of the Seasons: The Exploitation of Variations in Crop Seasonality Responses by Later Prehistoric Farmers - Jones, Martin K.; Lister, Diane L. (Frontiers in Ecology and Evolution, 2022)
Discussions of domestication and its associated genetic traits has focussed upon dispersal mechanisms, for example in the rachis structure of cereals. Here we consider another trait of importance to domesticated crops – their seasonality response. We particularly consider flowering response to changing daylength, and how that relates to domesticated species that are carried by farmers considerable distances from their regions of origin. We consider the implications of cultivating crops in regions whose seasonality patterns contrast with those of the crop’s region of origin, and consider the consequent genetic changes. Reference is made to the particular case of barley, and archaeogenetic research into its photoperiod response.